Effects of Meal Similarity on Interpersonal Synchronization in Three-Party Remote Dining - Wang, Jui-Ying; Kubota, Sho; Inoue, Tomoo (Frontiers in Computer Science, 2022)
In recent years, online commensality, such as remote dining, has become a way to connect people in different places. In remote dining, people have drinks, snacks, or meals while chatting with each other via video calls and seek connectedness and belonging. However, many people feel that there is a gap between real-life and digital co-eating and that interaction in current remote dining fails to satisfy the need for companionship. Unlike real-life co-eating, in remote dining, one’s meal may not be similar to that of a partner’s because people usually prepare their own food separately. In this study, we focused on the effects of meal similarity on interpersonal synchronization and subjective feelings. We conducted a laboratory-based remote dining experiment and video analysis to investigate whether eating similar meals in remote conditions has any effect on eating behavior and to explore the relationship between meal similarity, interpersonal synchronization, and subjective feelings. The results showed that participants ate at a faster pace and conducted eating actions more frequently. They were more synchronized with their partners, and the feeling of togetherness was stronger. Thus, we suggest that preparing similar meals or ordering the same dishes can enhance the remote dining experience.